Empathetic Visualizations: The Effect of Visualization Styles on Emotional Activation and Memorability of Insights - Aldesouky, Nadine (2022)
Dissertation presented as the partial requirement for obtaining a Master's degree in Data Science and Advanced Analytics, specialization in Business Analytics